Six new species of Elpidium Müller, 1880 (Podocopida: Limnocytheridae) from Eastern Brazil - Pereira, Julia S.; Da Rocha, Carlos E. F.; Martens, Koen; Pinto, Ricardo L.; Dasilva, Marcio B. (Zootaxa, 2023)
Elpidium is the most common ostracod genus occurring in phytotelmata in the Neotropical region, with distributions ranging from Florida, USA in the north to Rio Grande do Sul, Brazil in the south. However, the genus remains poorly known both in terms of diversity and of the distributional pattern of its species. Here, we describe six new species of Elpidium, E. oxumae n. sp., E. cordiforme n. sp., E. picinguabaense n. sp., E. eriocaularum n. sp., E. higutiae n. sp., E. purium n. sp., all from phytotelm environments in the Brazilian Atlantic rain forest. In addition, we discuss the distributional pattern and endemicity levels of Elpidium species in the light of these new taxonomic results and argue about possible misunderstandings on the distribution of the type species E. bromeliarum.